2017
DOI: 10.1007/s00270-017-1748-4
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Unibody Single-Branched Stent Graft for Patients with Type B Aortic Dissections Involving the Left Subclavian Artery: 1-Year Follow-Up Outcomes

Abstract: The single-branched stent graft was safe and efficient in the 1-year follow-up. Further studies are required to determine its long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…The endo-revascularization methods of aortic arch branches include in situ fenestration, 2 5 custom-made stent-grafts, 6 the chimney technique, 7 , 8 and branched stent-grafts. 9 Although these techniques can preserve the blood flow to the branches, they still have some shortcomings such as a long operation time, long physician learning curve, high risk of endoleakage, and low equipment availability. In situ fenestration requires a high number of specialized devices such as laser equipment, laser fibers, wires, catheters, and balloons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endo-revascularization methods of aortic arch branches include in situ fenestration, 2 5 custom-made stent-grafts, 6 the chimney technique, 7 , 8 and branched stent-grafts. 9 Although these techniques can preserve the blood flow to the branches, they still have some shortcomings such as a long operation time, long physician learning curve, high risk of endoleakage, and low equipment availability. In situ fenestration requires a high number of specialized devices such as laser equipment, laser fibers, wires, catheters, and balloons.…”
Section: Discussionmentioning
confidence: 99%
“…In the first decade of TEVAR, the LSA was always covered by a stent-graft when the proximal landing zone was not long enough. However, some studies [9][10][11] have shown that the LSA provides important circulation to the spinal cord, brain, and left upper extremity; therefore, covering the LSA with a stent-graft might not be inconsequential. Stroke, paraplegia, and coronary ischemia in the setting of a left internal mammary artery bypass as well as left upper extremity ischemia have been described in various reports.…”
Section: Discussionmentioning
confidence: 99%
“…If multiple reports described (partly) the same patient cohort, the most recent report was selected. A total of 14 studies were included, describing endovascular treatment of 302 patients with branched endografts (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Overall proportions were calculated with a meta-analysis of proportions in R version © Annals of Cardiothoracic Surgery.…”
Section: Current Techniques and Outcomes Of Branched Tevarmentioning
confidence: 99%
“…Several additional procedures have been implemented to preserve the supra-arch branches. [3][4][5][6][7] Compared to open surgery, a hybrid procedure is a less invasive approach to reconstruct the supra-arch branches and has more favorable outcomes in terms of lower mortality and morbidity. 3,4 Despite excellent technical success, a hybrid procedure is not acceptable for patients with severe comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Fenestrated/ branched TEVAR, as a totally endovascular approach, has emerged as a way to treat high-risk patients with unfavorable anatomy. [5][6][7] However, this approach has been criticized for its time-consuming manipulation and high medical expenses, and it is especially unsuitable in urgent/emergency settings.…”
Section: Introductionmentioning
confidence: 99%